Fostering Students’ Aesthetic and Creative Competencies through Painting in Higher Education - Sohibova Zuhroxon Akmal qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article investigates the role of painting in fostering students’ aesthetic and creative competencies in higher education. It analyzes pedagogical strategies, interactive learning methods, and the use of modern technologies to enhance students’ artistic expression, visual literacy, and problem-solving skills. The study emphasizes the importance of both individual and collaborative painting activities for comprehensive student development.